Relationship between fatty acid habitual intake and early inflammation biomarkers in individuals with and without type 2 Diabetes in Mexico - Guadarrama-López, Ana L.; Valdés-Ramos, Roxana; Kaufer-Horwitz, Martha; Harbige, Laurence S.; Contreras, Irazú; Martínez-Carrillo, Beatriz E. (Bentham Science Publishers, 2015)
Background: Lifestyle changes have led to a high global incidence of type 2 Diabetes mellitus (T2DM). Evidence suggests beneficial effects of the intake of n-3 and n-6 polyunsaturated fatty acids (PUFA) in patients with T2DM.